The dragon princess - Baker, E. D. (Bloomsbury, 2008)
Although a princess, Millie cannot keep herself from turning unexpectedly into a dragon, so she ventures off to the Frozen North to find the Blue Witch, who she hopes will help her learn to control her dragon magic.